1998
DOI: 10.1007/s002130050566
|View full text |Cite
|
Sign up to set email alerts
|

"Depression" increases "craving" for sweet rewards in animal and human models of depression and craving

Abstract: This study consisted of two experiments, one in rats and one in human volunteers, that used the identical progressive ratio (PR) operant procedure. In both experiments, responding was reinforced under a progressively increasing work requirement, and different groups of subjects received reinforcers that varied in sweetness. In experiment 1, rats were subjected to chronic mild stress, a well-validated animal model of depression. Performance under the PR schedule increased in subjects reinforced with conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
92
3
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 53 publications
15
92
3
11
Order By: Relevance
“…In this study, we observed that rats submitted to chronic administration of H-BCAA have a decreased sweet food intake and increased adrenal gland weight, without any alteration of body weight compared with the control group. This mimics anhedonia, a key depressive symptom (Katz et al 1981b;Willner et al 1987Willner et al , 1998. We also observed an increase in immobility time in the H-BCAA group during the forced swimming test.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, we observed that rats submitted to chronic administration of H-BCAA have a decreased sweet food intake and increased adrenal gland weight, without any alteration of body weight compared with the control group. This mimics anhedonia, a key depressive symptom (Katz et al 1981b;Willner et al 1987Willner et al , 1998. We also observed an increase in immobility time in the H-BCAA group during the forced swimming test.…”
Section: Discussionsupporting
confidence: 63%
“…18,19,30 It has been argued that performance under the PR schedule provides a measure of motivation to obtain specific foods rather then a measured hedonic value ('liking'). For example, alterations in mood affect performance under a PR schedule using chocolate as reinforcer in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alterations in mood affect performance under a PR schedule using chocolate as reinforcer in humans. 30 It is so far unknown, whether obese individuals differentially respond under a PR schedule.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that basic research in both animals and humans (Willner et al, 1998) has shown that subjects find sweet foods to be more reinforcing after depressive mood induction. There are wide individual differences in the influence of depression on body weight, with some people gaining weight while depressed and others losing weight (Barefoot et al, 1998).…”
Section: Depression and The Reinforcing Value Of Foodmentioning
confidence: 99%